Variability and trends in the Southern Hemisphere high latitude, quasi‐stationary planetary waves. (10th August 2016) - Turner, John; Hosking, J. Scott; Bracegirdle, Thomas J.; Phillips, Tony; Marshall, Gareth J.
ABSTRACT: We investigate variability and trends of the Southern Hemisphere quasi‐stationary planetary waves over 1979–2013 using the European Centre for Medium‐range Weather Forecasts (ECMWF) Interim reanalyses. The effects of tropical and extra‐tropical forcing factors on the phase and amplitude of the planetary waves are identified. The amplitudes of wave numbers 1–3 exhibit an annual cycle with a minimum in summer and maximum over the extended austral winter period. The phase of wave number 1 has a semi‐annual cycle, moving east in austral spring/autumn and west in summer/winter as a result of differences in the phase of the semi‐annual oscillation across the Pacific sector of the Southern Ocean. The phase of wave number 3 has an annual cycle, being more eastward (westward) in summer (winter). Year‐to‐year variability of the amplitude of wave number 1 is found to be strongly associated with the Amundsen Sea Low, which in turn is known to be strongly influenced by the El Niño–Southern Oscillation, with the consequence that the amplitude of wave number 1 is larger during the El Niño phase of the cycle. Regarding trends for the year as a whole, the amplitude of wave number 1 has decreased since 1979 ( p < 0.1), while the amplitudes of wave numbers 2 and 3 have increased. These changes are consistent with the warming trends in sea surface temperatures across much of the tropical oceans. However, the factors associated with longer‐term trends are less clear than for year‐to‐year variability.